An Ultrastructural Perspective on Cell Death - Najdawi, Zaid; Abu-Asab, Mones (Jordan Medical Journal, 2022)
In the field of cell death, there is still a wide gap between the molecular models and their ultrastructural phenotypes. Because only very few published works included electron microscopy (EM) images, many ultrastructural features have not yet been incorporated into the descriptions of death modes. Some of the EM features that appear in dying cells have not been incorporated in describing death modes. It includesthe accumulation of lipid droplets and glycogen, the appearance of extranuclear chromatin in the cytoplasm, and the various ways mitochondria become damaged. We argue that electron microscopy should be routinely included in these studies because it exposes some new features that molecular studies do not. It has successfully recognizednew modes of cell death,such as entosis, methuosis, and paraptosis. Elucidating the precise sequence of events in death modes could be the cornerstone for offering the proper therapy of many diseases by slowing down or stopping the progression of degeneration. This review presents our own experience applying ultrastructural interpretations to death modes and explainingtheir biochemical implications. We complement the molecular and biochemical data and point out missing features that shouldbe considered and studied.